Money Politics sebagai Kejahatan Pemilu Ditinjau dari Hukum Pidana Islam - Sadli, Sadli; Sukiati, Sukiati (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
Electoral crimes such as vote-buying and vote manipulation are serious offenses that undermine the democratic process and harm the fairness of elections. In positive law systems, perpetrators of these crimes face criminal penalties such as fines, imprisonment, or disqualification. Meanwhile, in Islamic law, such actions are viewed as forms of betrayal (khiyanah) or bribery (risywah), which may be subject to ta'zir punishments according to the judge's discretion. This study aims to compare the sanctions imposed by positive law and Islamic law on electoral crimes, as well as the moral and spiritual consequences faced by the perpetrators. The method used is a literature review of various sources of positive law and Islamic texts. The findings reveal that both positive law and Islamic law emphasize the importance of safeguarding the integrity of elections, with strict worldly penalties and warnings of severe consequences in the afterlife. Islamic criminal sanctions for perpetrators of election crimes be in the form of ta’zir, which is given at the discretion of the judge or ruler, such as fines or imprisonment. This research contributes to the understanding of election crimes from the perspective of Islamic criminal law, because ta'zir is a flexible criminal act and offers conflict resolution.